Meta-analysis of robotic versus open pancreaticoduodenectomy in all patients and pancreatic cancer patients - Fu, Yibo; Qiu, Jiangdong; Yu, Yiqi; Wu, Danning; Zhang, Taiping (Frontiers in Surgery, 2022)
Purposes: To compare perioperative outcomes of robotic pancreaticoduodenectomy (RPD) to open pancreaticoduodenectomy (OPD) using evidence from cohort studies. Methods: Outcomes of interest include operative time, blood loss, R0 resection rate, lymph nodes harvested, overall complication rate, pancreatic fistula rate, delayed gastric emptying rate and 90-day mortality. Results: 6 prospective studies and 15 retrospective studies were included. Five of these studies were limited to patients with pancreatic cancer. Operative time was significantly longer in RPD (WMD: 64.60 min; 95% CI :26.89 to 102.21; p = 0.001). Estimated blood loss was lower in RPD (WMD: -185.44ml; 95% CI: -239.66 to -131.21; p < 0.001). Overall complication rates (OR: 0.66; 95% CI 0.44 to 0.97; p < 0.001) and pancreatic fistula rate (OR: 0.67; 95% CI 0.55 to 0.82; p <0.001) were both lower in RPD. Length of hospital stay was longer in OPD (WMD: -1.90; 95% CI: -2.47 to -1.33). 90-day mortality was lower in RPD (odds ratio: 0.77; 95% CI 0.45 to 0.95; p =0.025). Conclusion: At current level of evidence, RPD is a safer alternative than OPD with regard to post-operative outcomes and blood loss. However, in terms of oncological outcomes RPD show no advantage over OPD, and the cost of RPD was higher. In general, RPD is now considered a reliable technology, but high-quality RCT studies are still needed to support this conclusion.